2001
DOI: 10.1017/s003329170100383x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic distress syndromes in later life: the need for paradigm change

Abstract: Somatic distress syndromes, which include somatoform disorders and syndromes of chronic fatigue such as neurasthenia but not somatic presentations of anxiety and depression, are one of the common expressions of distress in primary care (Ormel et al. 1994) and general hospital settings (Hemert et al. 1993). They are of considerable importance cross-culturally (Ono et al. 1999), and often lie at the interface of psychiatry and medicine (Hickie, 1999). They are associated with significant disability (Ormel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Overall rates of GMS psychiatric disorder and of physical disorder are consistent with those reported in other surveys (Royal College of General Practitioners, 1995 ;Copeland et al 1999). The possibility of confounding of somatization measures by physical disorder remains; no gold standard for measuring somatization in this population exists and measures must allow recognition of somatization in the presence of physical disorder (Wijeratne & Hickie, 2001). Finally, no younger control group was assessed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Overall rates of GMS psychiatric disorder and of physical disorder are consistent with those reported in other surveys (Royal College of General Practitioners, 1995 ;Copeland et al 1999). The possibility of confounding of somatization measures by physical disorder remains; no gold standard for measuring somatization in this population exists and measures must allow recognition of somatization in the presence of physical disorder (Wijeratne & Hickie, 2001). Finally, no younger control group was assessed.…”
Section: Discussionsupporting
confidence: 82%
“…Somatization has received little attention in older people (Sheehan & Banerjee, 1999 ;Wijeratne & Hickie, 2001). Reasons for this may include reluctance to diagnose somatization in the presence of physical illness (World Health Organization, 1992), a belief that neurotic disorders tend to decline with increased age (Krasucki et al 1998) and general confusion about the delineation of somatic syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Somatic symptoms are physical symptoms that cause distress yet lack an objective physical basis linked to psychological stress. Physical symptoms and somatization are core features of GAD among older adults (Caminero, Blumentals, & Russo, 2005;Lenze et al, 2005;Witherante, 2001;Yohannes et al, 2000); yet researchers have demonstrated differing results related to this association. In a study of the association between anxiety and medical symptoms, found that once they controlled for medical conditions, individuals with medical and anxiety disorders reported higher numbers of somatic symptoms compared to those with just a medical disorder.…”
Section: Physical and Somatic Influencesmentioning
confidence: 99%
“…These phenomena include, for example, general degenerative processes, a tendency to multimorbidity with increasing age, and frequent medication use, which can be accompanied by nonspecific side effects. Older people may also have difficulties in distinguishing symptoms from the background noise of the general somatic sensations they experience and might be more attached to biological models of illness and not take psychosocial factors into account as suggested by Wijerante and Hickie [55]. This separation of mind and body may lead to a neglect of accompanying psychological features that is further supported by clinicians who are also attached to a biomedical way of thinking.…”
Section: Dsm-v Somatic Symptom Disorder-a Helpful Solution?mentioning
confidence: 99%